Automatic prehension using an accelerometer and force sensor - Ahmad, Siti Anom; Chappell, Paul H.; Ali, Mohd Liakot (2005)
Controlling gripping force and object slippage is one of the main concerns in the prosthetic hand system. This paper describes a basic equation on a gripping force of an object in one dimension that has been formulated, where the time and the acceleration profiles are defined for holding the object securely. An accelerometer and force sensor system has been developed to monitor the gripping force and also sense the displacement of the object slippage. The acceleration when the object slips is observed and is double integrated to determine the velocity and then the distance. Experimental results are presented for the acceleration and the subsequent integrations. Having the necessary components identified, built and tested, the apparatus can be used to investigate automatic control algorithms for secure grips on objects.